2020
DOI: 10.1155/2020/5157046
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Solid Waste Dump Site on Surrounding Soil and River Water Quality in Tepi Town, Southwest Ethiopia

Abstract: An increase in urban population and the rising demand for food and other essentials perpetuate a rise in the amount of waste being generated daily by each household. In Ethiopia, this waste is eventually thrown into open dump sites. It can cause severe impact on soil and surface water quality. As a result, it becomes the probable source of human health risk through food chain. Therefore, this study was aimed at assessing the effect of a solid waste dump site on surrounding soil and river water quality in Tepi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…e levels of Cd and Cu may be related to the high levels of these metals in the waste which are disposed of at the landfill [51]. Mekonnen et al found that Pb, Cd, Mn, Ni, Cu, and Zn were found in the leachate water [52]. Moreover, approximately 62% of the total fresh municipal solid waste was found to be combustible materials including plastics, paper, yard waste, textile, cardboard, rubber, and coconut husks [51].…”
Section: Concentrations Of Heavy Metalmentioning
confidence: 99%
“…e levels of Cd and Cu may be related to the high levels of these metals in the waste which are disposed of at the landfill [51]. Mekonnen et al found that Pb, Cd, Mn, Ni, Cu, and Zn were found in the leachate water [52]. Moreover, approximately 62% of the total fresh municipal solid waste was found to be combustible materials including plastics, paper, yard waste, textile, cardboard, rubber, and coconut husks [51].…”
Section: Concentrations Of Heavy Metalmentioning
confidence: 99%
“…Due to the concentration of industries, an urban population growth, the consumption of residents, and inadequate finance and facilities, the volume of waste was increased in urban areas of SNNPR [ 12 ]. In Tepi town, the generated solid wastes were thrown away on streets, unapproved dumpsites, in waterways (drainage systems), and at open sites near the residential areas affecting the environment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of variance (ANOVA) was used to assess the significance difference between the mean values of organochlorine and organophosphate pesticide residues in sample cereal crops. Possibilities less than 0.05 ( p < 0.05) were considered statistically significant, and the analyzed data was presented by using tables [ 36 ]. All the mean values of organochlorine and organophosphate pesticide residues were compared with maximum pesticide residual limits in food samples established by Codex Alimentary and European Union standards [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%